Short-term real-world outcomes of diabetic macular edema treated with intravitreal faricimab. - Toshiaki Hirakata; Fumihiro Hara; Yuta Nochi; Daisuke Shinohara; Shutaro Yamamoto; Yoshimune Hiratsuka; Shintaro Nakao (PLoS ONE)
Faricimab, a new drug for diabetic macular edema (DME), was made available in Japan in 2022. However, few reports have been published about its treatment outcomes in clinical practice. To assess the short-term outcomes of intravitreal faricimab (IVF) in patients with DME, the records of patients with DME receiving IVF therapy between July 2022 and July 2023 at Juntendo University Hospital were retrospectively reviewed. Their best-corrected visual acuities in the logarithm of the minimum angle of resolution units and central macular thicknesses were compared at baseline and one month after the final IVF. Eighteen patients and 22 eyes were included and allocated to the naïve and switched groups: 12 cases (15 eyes) and 6 cases (7 eyes), respectively. The best-corrected visual acuity improved for the naïve group, but no difference was observed for the switched group. In contrast, the central macular thickness improved for both the naïve and switched groups. IVF demonstrated good short-term outcomes for DME, suggesting that it is effective for DME in clinical practice.